P486 Faecal microbiota transplantation in inflammatory bowel disease: the patient's perspective. (25th January 2019) - Sousa, M; Ponte, A; Rodrigues, J; Silva, J; Gomes, C; Rodrigues, A; Silva, A P; Carvalho, J
Abstract: Background: Faecal microbiota transplantation (FMT) is recognised as effective and safe for Clostridium difficile infection, leading to the study of its application in other diseases, including inflammatory bowel disease (IBD). In a recent meta-analysis clinical remission was reported in 45% of patients undergoing FMT in IBD. However, it is important to understand the patient's perspective, namely on the knowledge on FMT and its acceptability. Methods: One hundred consecutive outpatients with IBD answered a written questionnaire consisting of 3 parts: (1) 5 questions prior to reporting on FMT; (2) FMT information leaflet on IBD; (3) 5 questions after reading the leaflet. Results: Of the 100 patients included, 51% had Crohn's Disease and 49% ulcerative colitis. The majority of patients considered their disease to be moderate (n = 57) and 25 patients reported fear of current medication mainly due to the risk of neoplasia (n = 11) or infections ( n ​​= 6). The majority of the patients (89%) were unaware of FMT and without previous information 24% would accept FMT. The main reasons for the refusal were fear of infection ( n = 19), disgusting ( n = 10) and lack of information ( n = 7). After reading the information leaflet, the acceptance percentage was 40% and if the treating physician stated that FMT was the best treatment, the percentage increased to 73%. When asked if they would prefer FMT or an experimental new drug, 36% preferred FMT, 36% new drug and 28% did not respond. Regarding the route of administration, the majority ( n = 59) preferred colonoscopy. Conclusions: TMF may be a promising therapy in IBD, but it is necessary to provide information and awareness to patients for the procedure. In our sample, we concluded that most patients were unaware of TMF, but would be willing to perform the procedure if properly informed by their physician.